A note on generalized finite Hankel transforms of the second and third kind - Bermúdez, Misvely (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper generalized Hankel finite transforms of the second and third kind are defined by using the Shurm-Liouville finite transform theory. Its Inversion formulas are given and their application to a problem related to atmospherical pollution.